The Influence of Capital, Labor, and Technology on MSME Performance with the Implementation of Digital Accounting as a Moderating Variable - Syah, Syafrial; Rahmawani, Rahmawani; Tanjung, Adetia Azmi (Dinasti Publisher, 2024)
The purpose of this study is to determine the effect of capital, labor and technology on the performance of MSMEs with the application of digital accounting as a moderating variable. This study was conducted on 100 respondents of MSME owners in Asahan Regency. The analysis of this study uses PLS and NVIVO. The results of this study areFrom the results of the study above, it can be seen that there is an influence between the Capital (X1) and Labor (X2) variables on Y, while the Technology (X3) variable shows that the results have no effect on the MSME Performance variable (Y). The moderation variable, namely Digital Accounting, does not moderate the Capital (X1) and Technology (X3) variables on Y. because the value obtained is above alpha. From the results of NVIVO processing, it can be seen that the application of digital accounting by MSMEs is due to easier use in preparing financial reports.